State Interest and the State-Centered Approach to Competition Law in China. (June 2020) - Ng, Wendy
There have long been concerns and speculation that China's competition authorities are using the Anti-Monopoly Law (AML) to pursue public interest objectives and prioritizing them over competition. This article explores whether and how public interest factors are relevant to the administrative enforcement of the AML. It shows that, rather than public interest, it is "state interest" and China's state-centered approach to competition law that more aptly explains the AML and its administrative enforcement.